The Influence of Price, Facilities, and Service Quality on Parental Satisfaction (At Nurul Huda Elementary School in Surabaya City) - NURLAILIYAH, Shinta (International Journal of Environmental, Sustainability, and Social Science, 2025)
This study aims to further examine the "Influence of Price, Facilities, and Service Quality on Parent Satisfaction" at MI Nurul Huda. The main issue addressed is the relationship between these three variables and the level of parent satisfaction. The background of this research is driven by parents' high expectations regarding educational quality and provided facilities, as well as the role of price, which is expected to align with service quality. The objectives are to analyze the individual impact of price, facilities, and service quality on customer satisfaction, as well as their combined (simultaneous) effect on overall parent satisfaction. A quantitative method with a survey approach was used, employing questionnaires distributed to parents of students from grades 1 to 6. The population consisted of all students at MI Nurul Huda, with a sample of 80 respondents selected using the Slovin formula. Data analysis involved multiple linear regression, and validity was tested using Spearman's Rank correlation. The results show that, in summary, neither price nor facilities significantly affect parent satisfaction, whereas service quality has a positive and significant impact. Additionally, the three variables together significantly influence the level of parent satisfaction. The conclusion is that service quality is the main factor affecting parent satisfaction. Although price and facilities do not have a significant effect individually, they contribute to overall satisfaction when combined.